Analisis Pesan Dakwah Dalam Film Preman Pensiun Kesempatan Kedua Tahun 2020 - Muhammad Asyraf Firmansyah; Choiriyah; Muslimin (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
One of the instruments and medium that is particularly efficient at everything, including spreading messages of da'wah, is film. Da'wah messages, which derive from the Al-Qur'an and As-Sunnah, are Islamic teaching tools that address all facets of life in terms of aqidah, sharia, and morals. Dakwah activities in the millennial era have recently been more in touch with the film industry. Preman Pensiun Second Chance is one of the movies with a missionary theme. This movie combines the drama, comedy, crime, and action genres. The issue that the author will look at in the movie Preman Pensiun Prestasi Second is how the construction of the meaning of da'wah in the movie Preman Pensiun Prestasi Second and descriptive qualitative methods are used in this study. Roland Barthes' semiotic analysis is also used in this study. According to the findings of this study, the film Second Chance Pensiun Preman contains one scene that preaches aqidah principles, one scene that preaches sharia principles, and one scene that preaches moral principles. Preman Pensiun Second Chance uses one scene each of aqidah, sharia, and morality to establish the meaning of its da'wah, in contrast.